Interactive Education Mobile Game Application: Petah Simpulan Bahasa - sulaiman, suzidiana (Journal of Computing Technologies and Creative Content, 2019)
Abstract—"Simpulan Bahasa" which are commonly used amongst Malaysian people are a combination of two or three words that have a different meaning from the basic words. Thus, the importance of the "Simpulan Bahasa" in sustaining the Malaysian language cannot be denied and must be maintained and learned by the next generation. However, "there are serious questions regarding the effectiveness and student's engagement of this conventional lecture approach because studying and memorizing the concepts from the teachers' note is considered as an ineffective way of teaching." (Aisyah Abdul Manap, 2013 [1]). Therefore, the purpose of this research is to develop an interactive education mobile game as an instrument for improving learning and mastery of the "Simpulan Bahasa" for the students.